PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN BIOLOGI KELAS X SMA - Al Dina Rahmi; Nofri Hendri; Ida Murni Saan (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
This study aims to produce interactive multimedia product in Biologi class X high school subject that are valid and practical. This type of reseacrh is  development research or better known as Research and Development (R & D). The research use development model 4 – D (Four D). The development produce in the researchthe research consisted of 4 stages: define, design, develop, and dissiminate. The validity test of product is done by 3 validator, they are two media expert validator and one material expert validator. Product trial are conduct on 20 student grade X MIA-2  at SMA Negeri 1 Kecamatan Guguak Kabupaten Lima Puluh Kota with the aim to knowing the practically of the product being develop. The instrument of the research than use are questionnaire, documentation, and research format.The result of the material validity was find the mean 4.31 with presentage 86% categorized very well, and the result of the media was find the mean was 4,44 with presentage 89% categorized very well. Product praticality test result was find 4,40 with presentage 88% categorized very well. So that, the writer can concluded that the product of interactive multimedia can be use on learning by the student because suitable with meid eligibility criteria.